2022
DOI: 10.3390/md20060365
|View full text |Cite
|
Sign up to set email alerts
|

Protein Hydrolysate from Spirulina platensis Prevents Dexamethasone-Induced Muscle Atrophy via Akt/Foxo3 Signaling in C2C12 Myotubes

Abstract: Loss of muscle mass is the primary symptom of sarcopenia. Protein intake is recommended to prevent muscle mass loss, and Spirulina platensis, a microalga with high protein content, is a potential protein supplement. Here, we evaluated the differentiation ability of C2C12 cells and the inhibitory effect of Spirulina hydrolysates (SPH) prepared by Collupulin on dexamethasone (DEX)-treated C2C12 cells. SPH contained 578.27 mg/g protein and 92.30 mg/g branched-chain amino acids. SPH increased C2C12 myotube length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…And, SPH was determined to suppress muscle atrophy in C 2 C 12 cells through up-regulating MyoD1, Myf5, and myogenin and inhibiting Atrogin-1 and MuRF-1 to inhibit the Akt/FoxO3a signaling pathway. 91 Similarly, the antisarcopenic peptide from whey protein was also reported to play a key role via this mechanism. After confirming the antisarcopenic activity of WP-S, Shin et al 67 investigated its underlying molecular mechanism.…”
Section: Bioavailability Of Antisarcopenic Peptidementioning
confidence: 95%
See 3 more Smart Citations
“…And, SPH was determined to suppress muscle atrophy in C 2 C 12 cells through up-regulating MyoD1, Myf5, and myogenin and inhibiting Atrogin-1 and MuRF-1 to inhibit the Akt/FoxO3a signaling pathway. 91 Similarly, the antisarcopenic peptide from whey protein was also reported to play a key role via this mechanism. After confirming the antisarcopenic activity of WP-S, Shin et al 67 investigated its underlying molecular mechanism.…”
Section: Bioavailability Of Antisarcopenic Peptidementioning
confidence: 95%
“…Lee et al reported that the expression levels of Atrogin-1 and MuRF-1 were decreased in C 2 C 12 cells treated with PYP1-5, showing the potential mechanism of PYP1-5 to suppress MPD via UPP. And, SPH was determined to suppress muscle atrophy in C 2 C 12 cells through up-regulating MyoD1, Myf5, and myogenin and inhibiting Atrogin-1 and MuRF-1 to inhibit the Akt/FoxO3a signaling pathway . Similarly, the antisarcopenic peptide from whey protein was also reported to play a key role via this mechanism.…”
Section: Mechanism Of Antisarcopenic Peptides In Alleviating Sarcopeniamentioning
confidence: 99%
See 2 more Smart Citations
“…MYH7 and Desmin are two key proteins for the sarcomere structure and were significantly increased in the tFNAs treatment groups. To better understand the impact of DEX and tFNAs treatment on myogenic regulating factors, we measured the mRNA expression levels of MyoD and MyoG, the initial transcription factors for the differentiation of myocytes, along with Atrogin and MuRF1 that are related to muscle cell senescence . We detected that the expressions of MyoD and MyoG were both suppressed in the DEX group while Atrogin and MuRF1 were highly expressed.…”
Section: Tfnas Ameliorate Muscle Atrophy and Enhance Muscle Strength ...mentioning
confidence: 99%